Al-Islam Hospital human resource system - Muhammad, Muhd. Rosydi; Ali Munassar, Fatima Hasan (IIUM Press, 2011)
This chapter represents a useful system that provides a flexible way for Human Resource (HR) Unit to implement its duties. HR department is one of the most important bodies in the hospital that holds various duties. Until recently, the operations at HR department of the hospital are done manually. This web-based Human Resource system has been designed for AI-Islam Specialist hospital to automate the leave application and management process, as well as simplifying the tasks and reducing the workloads of Human Resource department. Parts of HR duties are handled by this system; which are leave application system and staff processing data system. Enabling online leave application has added an advantage to HR unit as well as staff. It helps to ease the process of applying, tracking and endorsing leave application. Staff processing data system is another useful way to smooth the process of keeping records, retrieving and modifying staff data. This new system is expected to facilitate portions of HR functions and duties and consequently improve HR department performance